Bibliometric Study on the Relationship between Entrepreneurship Education and Business Sustainability - Judijanto, Loso; Arisanti, Ivon; Devi, Erwina Kartika; Aris, Nurlina; Mardiah, Ainil (Westscience Press, 2025)
Entrepreneurship education has emerged as a crucial driver of innovation and business sustainability, equipping individuals with the necessary skills to navigate complex market environments while fostering responsible and sustainable business practices. This study conducts a bibliometric analysis using Scopus database and VOSviewer to map the evolution of research at the intersection of entrepreneurship education and business sustainability. The analysis identifies key research trends, influential authors, collaborative networks, and emerging thematic areas, providing insights into how scholarly discourse in this field has developed over time. The findings reveal that entrepreneurship education research has expanded from individual behavioral studies to encompass pedagogical advancements, sustainability integration, and digital transformation through artificial intelligence and big data applications. While the study highlights strong international collaborations, it also uncovers regional disparities and limited interdisciplinary research, suggesting the need for more cross-country comparative studies and integration of sustainability-focused educational models. This study contributes to the academic discourse by identifying research gaps and proposing future directions for enhancing entrepreneurship education’s role in sustainable business development.